Accelerometer application mathematical model - Benevičius, Vincas; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2023)
The positioning problem considered in this paper is an attempt to find system’s of a few points position using accelerations. Today’s industry provides with various types of accelerometers suitable for acceleration measure. That data may be used to trace object movement.Final results showed that such movement trace is possible and may be applicable. The results also showed origins for errors which according to the results, are quite high globally. The final conclusion follows: the model created must be analized further in a deeper level, and error origins must be eliminated or at least minimized by either chosing different solving or modeling methods, either by revising used ones.
Keywords: positioning problem; accelerometer; modeling; system of differential equations